2016
DOI: 10.1038/nrd.2016.151
|View full text |Cite
|
Sign up to set email alerts
|

Targeting hepatic glucose metabolism in the treatment of type 2 diabetes

Abstract: Type 2 diabetes mellitus is characterized by the dysregulation of glucose homeostasis resulting in hyperglycemia. Although current diabetes treatments have exhibited some success in lowering blood glucose, their effect is not always sustained and their use may be associated with undesirable side effects, such as hypoglycemia. Novel diabetic drugs, which may be used in combination with existing therapies, are therefore needed. The potential of specifically targeting the liver in order to normalize blood glucose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
260
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 295 publications
(265 citation statements)
references
References 256 publications
(320 reference statements)
3
260
0
2
Order By: Relevance
“…Our data show that expression levels of transcriptional activators FoxO1, HNF-4α, and PGC-1α were increased both in the liver and renal cortex in db/db mice. Accumulating evidences demonstrates that the expression or the promoter-binding activity of FoxO1, HNF4, PGC-1α or cAMP responsive element binding protein (CREB), which bind to the G6Pase and PEPCK1promoters, regulate gluconeogenesis in the liver [27, 31-35]. Recently, the transcriptional regulators of hepatic gluconeogenesis are also considered to be potential therapeutic targets for the treatment of T2DM [27, 35, 36].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our data show that expression levels of transcriptional activators FoxO1, HNF-4α, and PGC-1α were increased both in the liver and renal cortex in db/db mice. Accumulating evidences demonstrates that the expression or the promoter-binding activity of FoxO1, HNF4, PGC-1α or cAMP responsive element binding protein (CREB), which bind to the G6Pase and PEPCK1promoters, regulate gluconeogenesis in the liver [27, 31-35]. Recently, the transcriptional regulators of hepatic gluconeogenesis are also considered to be potential therapeutic targets for the treatment of T2DM [27, 35, 36].…”
Section: Discussionmentioning
confidence: 99%
“…Endogenous glucose production is mainly derived from two pathways: gluconeogenesis and glycogenolysis, both of these are enhanced in T2DM and contribute to fasting and postprandial hyperglycemia [27, 28]. In addition to the liver, the renal cortex also has the highest expression of enzymes related to gluconeogenesis and is therefore capable of generating considerable amounts of glucose (by gluconeogenesis) to be released into the circulation [29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whereas during fasting, hepatic gluconeogenesis is triggered to keep normal blood glucose levels. Under pathological conditions, hepatic gluconeogenesis is abnormally over-activated, which results in hyperglycemia and contributes importantly to the pathogenesis of various metabolic disorders, such as type 2 diabetes (T2D) (2,3). Previous studies have demonstrated that hepatic gluconeogenesis, rather than glycogenolysis, is increased in patients with T2D (2).…”
Section: Introductionmentioning
confidence: 99%
“…Under pathological conditions, hepatic gluconeogenesis is abnormally over-activated, which results in hyperglycemia and contributes importantly to the pathogenesis of various metabolic disorders, such as type 2 diabetes (T2D) (2,3). Previous studies have demonstrated that hepatic gluconeogenesis, rather than glycogenolysis, is increased in patients with T2D (2). Hepatic gluconeogenesis is largely controlled through key rate-limiting enzymes in the gluconeogenic pathway, specifically phosphoenolpyruvate carboxykinase (PEPCK) and glucose-6-phosphatase (G6Pase) (4).…”
Section: Introductionmentioning
confidence: 99%